Towards a Latin American NIME Research Community - Avila, Juan Pablo Martinez; Tragtenberg, João; Calegario, Filipe; Ramos, Juan; Lerner, Martin Matus; Corintha, Isabela; Jaimovich, Javier; Dannemann, Teodoro; Cadavid, Patricia; Alarcón, Ximena; Marquez-Borbon, Adnan; Solis, Hugo; et al. (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
In this workshop, we propose the first steps towards consolidating a Latin American (LATAM) New Interfaces for Musical Expression (NIME) Research Community. We aim to start a discussion and generate ideas around shortterm actionable initiatives that a LATAM NIME Research Community could explore in the near future. We will discuss various topics centered around three main areas: (1) The creation of a LATAM NIME network, (2) Exploring LATAM NIME perspectives, and (3) the Next Steps for LATAM NIME. After this activity, we will have a plenary discussion where we will share ideas for action and reflections. Lastly, we list a series of expected outcomes of the workshop, although we acknowledge that many others may emerge during the workshop. We look forward to taking the first steps towards a LATAM NIME Community and the future of this community within and beyond NIME, opening to other communities in LATAM, and stirring policy changes to support the development of our local communities.